Phylogenetic Analysis of ftsZ in Wolbachia: Implications for Host Specificity - Rovik, Anwar; Rahayu, Ayu (Makara Journal of Science, 2025)
Wolbachia are the most prevalent and successful endosymbiont in invertebrates and are categorized into 21 supergroups based on genetic phylogeny. The filamenting temperature-sensitive Z (FtsZ) protein is essential for bacterial cell division and is hypothesized to play a role in Wolbachia's control of host reproduction. However, despite FtsZ's importance, little is known about its diversity and function within Wolbachia. This study investigated the variability of the FtsZ-encoding gene among Wolbachia strains and their hosts. FtsZ gene sequences were retrieved from the National Center for Biotechnology Information database, and representative sequences were randomly selected from each host species and analyzed for phylogenetic relationships. A total of 1–10 sequences for each of the Wolbachia strains infecting the various hosts were included in the analysis. The ftsZ gene sequences ranged from 450 to 970 base pairs, with a consensus sequence of 520 base pairs. Phylogenetic analysis revealed substantial genetic divergence in the ftsZ gene among Wolbachia strains from different host species. In contrast, Wolbachia strains within the same host species exhibited a lower level of genetic variation, which indicates that the gene pool within populations is relatively homogeneous.